2016
DOI: 10.1016/j.jbiomech.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anesthesia and fluid–structure interaction on simulated shear stress patterns in the carotid bifurcation of mice

Abstract: Segers, the Influence of anesthesia and fluid-structure interaction on simulated shear stress patterns in the carotid bifurcation of mice, Journal of Biomechanics, http://dx.doi.org/10. 1016/j.jbiomech.2016.06.010 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
8
11
0
Order By: Relevance
“…The difference in the PSF mainly is that the non-compliant artery wall model yields sharper transitions between low and high permeability regions, where in contrast the compliant artery wall does produce broader and more blurred high permeability regions. Similar observations for the WSS patterns in carotid arteries were observed in [20]. However, in [20] a significant influence of the compliant artery wall to the OSI was observed which lies in contrast to our observations.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…The difference in the PSF mainly is that the non-compliant artery wall model yields sharper transitions between low and high permeability regions, where in contrast the compliant artery wall does produce broader and more blurred high permeability regions. Similar observations for the WSS patterns in carotid arteries were observed in [20]. However, in [20] a significant influence of the compliant artery wall to the OSI was observed which lies in contrast to our observations.…”
Section: Discussionsupporting
confidence: 51%
“…Similar observations for the WSS patterns in carotid arteries were observed in [20]. However, in [20] a significant influence of the compliant artery wall to the OSI was observed which lies in contrast to our observations. Still we also support the idea that a FSI-like approach to model atherosclerosis is indispensable.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Another limitation pertains to the computational methods that were applied to determine the OSI. Recent work has indicated the importance of the buffering capacity of the carotid bifurcation on the computed OSI level, and they concluded that for accurate OSI computations fluid–structure interaction (FSI) simulations were required [39]. Whether FSI simulations would also influence the OSI values immediately upstream of the cast needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%